Revolutionizing Project Resilience through Advanced Risk Mitigation Strategy Launched: Merevolusi Ketahanan Proyek melalui Strategi Mitigasi Risiko Tingkat Lanjut Diluncurkan - Oktaviana, Hanifah; Jakaria, Ribangun Bamban (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the risks associated with project delays in the Mover Tram rail line repair project at TMII and proposes mitigation strategies using a combination of Risk Breakdown Structure (RBS), Analytical Network Process (ANP), and Bow Tie Analysis methodologies. Through expert interviews, questionnaires, and document analysis, key risks were identified and prioritized. Results indicate that construction management emerged as the dominant risk group, with specific risks including delays in critical path tasks and discrepancies between drawings and methods. Mitigation strategies were developed focusing on these dominant risks. The study underscores the importance of integrating diverse risk assessment techniques for effective project management and suggests avenues for future research to enhance risk management frameworks in construction projects. Highlights: 1. Integrated risk analysis enhances project resilience.2. Construction management pivotal for identifying and mitigating project risks.3. Future research: Explore cost-related risks for improved project outcomes. Keywords: Project delays, Risk management, Construction projects, Mitigation strategies, Analytical methodologies